A Stronger Effect of Body Mass Index and Waist Circumference on the Prevalence of Uncontrolled Hypertension among Caucasian Men than Women - Anna Chudek; Aleksander Jerzy Owczarek; Joanna Ficek; Magdalena Olszanecka-Glinianowicz; Katarzyna Wieczorowska-Tobis; Zofia Walencka; Agnieszka Almgren-Rachtan; Jerzy Chudek (Karger Publishers, 2021)
Background: Gender-related differences in fat distribution may affect blood pressure (BP) control in hypertensive subjects. The aim of the study was to assess how body mass (BM), BMI, and waist circumference (WC) influence the effectiveness of antihypertension therapy in hypertensive men and women in daily clinical practice. Patients and Methods: The observational study involved 12,289 adult hypertensive Caucasians (6,163 women) declaring regular use of antihypertensive drugs. BP control was scored based on the mean values of 2 attended office BP measurements. WC thresholds for visceral obesity were adopted from definitions of the International Diabetes Federation (≥94/80 cm for men/women) and National Cholesterol Education Program Adult Treatment Panel III (≥102/88 cm for men/women). Stepwise backward multivariable logistic regression was used to analyse correlates of the effectiveness of hypertension therapy. Results: The predictive value of BMI ≥30 (for uncontrolled hypertension) was stronger than that of visceral obesity, regardless of the criteria used. In men, BP control rapidly deteriorated with BMI (odds ratio [OR] up to 8.58 [95% CI: 5.74-12.83]) and WC (OR up to 5.09 [3.84-6.74]), while in women, the association was more flattened (OR up to 3.63 [2.78-4.74] and 1.93 [1.59-2.35], respectively). However, the highest risk of uncontrolled BP occurred in women with BM ≥110 kg (OR = 10.47 [5.05-21.71]) and men with BM ≥125 kg (OR = 9.66 [5.86-15.94]). Conclusions: (1) Obesity and visceral obesity limit the effectiveness of antihypertension therapy more in men than in women. (2) This phenomenon should be taken into account in the prescription of adequate doses of antihypertensive drugs.